Persistance of maternal antibodies in piglets from sows immunized with an inactivated oil-emulsion vaccine against Aujeszky's disease - Romero, Carlos H.; Flores, Robis S. (Pesquisa Agropecuaria Brasileira, 2014)
Duroc, Hampshire, Landrace and Largo White sows were immunized between the 70th and 90th days of one, two or three successive gestations with an inactivated oil-emulsion vaccine against Aujeszky's disease. The levels of neutralizing antibodies in the sows were evaluated at two and 16 weeks after farrowing. Similarly, the levels of neutralizing antibodies in their piglets were determined at two, four, six, eight, ten, twelve, fourteen and 16 weeks of age. At two and 16 weeks after farrowing, respectively, only 18.8% and 44.4% of the sows vaccinated once had neutralizing antibodies while one hundred percent of sows vaccinated twice and tested two and 16 weeks after farrowing were positive. On the other hand, 78.6% and 75% of the sows vaccinated three times posessed antibodies, respectively, two and 16 weeks post farrowing. Neutralizing antibodies of maternal origin were demonstrable in the piglets from the second week of life onwards. Those antibodies were present only in the piglets of sows with antibodies. In piglets of sows vaccinated only once, maternally-derived antibodies persisted up to the 10th or 12th week of life, while in piglets of sows vaccinated two or three times, those antibodies persisted a maximum of fourteen weeks.